Buprenorphine and cannabidiol co-administration reduces survival in a mouse model of orthopedic trauma - Bouchard, Caroline; Frégeau, Geneviève; Massé, Ian; De Beaumont, Louis (Frontiers in Pharmacology, 2025)
IntroductionAnalgesic selection following orthopedic trauma presents unique challenges due to potential drug interactions and physiological stress. The impact of different analgesic regimens - buprenorphine, cannabidiol (CBD), their combination, or vehicle - on survival was investigated in a murine model of tibial fracture.MethodsEighty male C57BL/6 mice were randomly assigned to one of four group: (1) Buprenorphine (0.1 mg/kg, administered subcutaneously every 12 h for 3 days) plus cannabidiol (CBD, 100 mg/kg, administered intraperitoneally once daily for 7 days); (2) CBD only; (3) Buprenorphine + vehicle; or (4) Vehicle only. All animals also received carprofen (20 mg/kg, subcutaneously, once daily for 3 days). Survival was monitored over 7 days post-injury, and necropsies were performed to identify probable causes of death.ResultsFollowing an orthopedic trauma, mice that received buprenorphine plus CBD exhibited significantly lower survival than those that received either treatment alone or vehicle only (p = 0.0049 and p = 0.02, respectively). No differences were noted between the other groups. Necropsy revealed gastrointestinal complications in most fatalities, while two deaths were linked to acute respiratory arrest post-injection.DiscussionThese findings suggest that while buprenorphine and CBD are individually well-tolerated, their co-administration may increase the risk of adverse outcomes in murine orthopedic trauma models. Combining cannabinoids and opioids in translational research requires caution and emphasizes the need for mechanistic evaluation in preclinical models.